FORMULATION OF UNDERGRADUATE TEACHER EDUCATION CORE COMPETENCIES: A HARMONIZATION APPROACH - Cahapay, Michael B. (PEOPLE: International Journal of Social Sciences, 2021)
The expectations for teacher education can sometimes be diverging, which can be addressed through a harmonization approach. This paper is a preliminary analysis that aims to formulate a set of competencies for teacher education by harmonizing different curriculum sources. Using document analysis as a research method, the Association of Southeast Asian Nations (ASEAN) teachers competency framework, Commission on Higher Education (CHED) program outcomes, and Department of Education (DepEd) professional standards for teachers were examined. The results showed unique, common, and different teacher expectations. Based on this result, seven core competencies were proposed underscoring content knowledge, learner diversity, learning environment, educational foundations, instructional development, community linkages, and personal and professional development. As part of the initial stage in the rigorous process of curriculum development, the results of this work should further undergo validation in the future.